Characterization and evaluation of Portuguese Opuntia spp. germplasm - Reis, C.M.G. (2018)
The main objectives of this thesis were to characterize and evaluate Portuguese Opuntia spp. ecotypes for biomass production and the cladodes nutritional quality for fodder, and for fruit yield and quality. In addition, the genetic diversity was assessed with nuclear microsatellite (nuSSR) markers. The plant vigour and biomass production were evaluated in germplasm of O. ficus-indica by non-destructive methods, 3 years following planting. Among ecotypes, significant differences were found in the studied biomass-related parameters and several homogeneous groups were established. In the case of the cladodes nutritional profile significant, differences were found in the crude protein and the ash content, and different groups were unfolded. In general, O. ficus-indica has a low dry matter content, crude protein, and neutral detergent fiber, and high content in non-fiber carbohydrates and metabolizable energy. Fruit production was evaluated in the second and third years after plantation. Significant differences were found among O. ficus-indica ecotypes, and different groups were established. The Italian cultivars “Gialla” and “Bianca” had highest fruit yield than Portuguese ecotypes. Besides, the morphology, bioactive compounds and antioxidant properties of fruits were studied in twenty ecotypes belonging to the species O. ficus-indica, O. robusta, O. dillenii and O. elata. The fruits displayed variability in morphological and bioactive characteristics. The analysis of genetic diversity using nuSSR markers within a set of 19 ecotypes, belonging to the four previously-mentioned species, was undertaken. The hierarchical clustering analysis revealed four major groups that clearly disentangled the Opuntia spp. species. Two subclusters were found considering the O. ficus-indica ecotypes. The results revealed a low level of genetic diversity among the ecotypes of O. ficus-indica.